The Roots of Reciprocity: Gratitude and Reputation in Generalized Exchange Systems. Issue 1 (February 2018) - Simpson, Brent; Harrell, Ashley; Melamed, David; Heiserman, Nicholas; Negraia, Daniela V.
Social scientists often study the flow of material and social support as generalized exchange systems. These systems are associated with an array of benefits to groups and communities, but their existence is problematic, because individuals may be motivated to take from the system without giving back to it. Researchers have identified two broad processes governing prosociality in generalized exchange systems: generalized reciprocity (a person who receives help from someone pays it forward by helping a third person) and indirect reciprocity (a person who helps another establishes a prosocial reputation and, as a consequence, later receives help from a third person). Although generalized exchange systems can be based on either process, generalized and indirect reciprocity are based on different mechanisms and, with few exceptions, have been investigated independently. Here we present an integrated approach to generalized exchange that (1) specifies when each process is most likely to promote prosocial behavior, (2) details the implications for resource inequalities in generalized exchange systems, and (3) describes how generalized and indirect reciprocity jointly influence prosocial behavior. Results from four new experiments strongly support the theoretical arguments.